1977
DOI: 10.1007/bf01072858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on electrical parameters of thein vivo rat stomach

Abstract: The gastric transmural electrical potential difference (PD) and direct-current resistance were measured in the rat in vivo under conditions in which the luminal pH was controlled over the pH range 1.0 to 12.0. Raising the pH above 11.0 caused a reduction in both PD and resistance. This is consistent with basic groups limiting cation permeability through the mucosa. Exposure of the mucosa to 20% ethanol caused a reduction in resistance, PD, and H+ secretion, and an increased appearance of Na+ in the lumen at ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1980
1980
1992
1992

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…Although there was a marked decrease in PD when ethanol was incubated at the mucosal side of the chamber, there were no significant changes in R and I. These findings are in contrast to other studies using a concentration of ethanol as high as 20 % [7,14] but they are in accord with the report by Saario et al [15] who reported that only concentrations greater than 30% elevated the R in the frog stomach. Submucosal ethanol exposure at 20% significantly decreased I but increased R. The depression of I is probably due to the interference of ion movement of electrical charges through cell membrane followed by a decrease in conductance (an increase in R), or dehydration of tissue, thus, leading to increase in R. It is believed that ethanol approaches the glandular mucosa more easily from the submucosal side (in the absence of epithelial barrier) than from the mucosal side, because the latter is protected by the epithelial cells and tight junctions.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Although there was a marked decrease in PD when ethanol was incubated at the mucosal side of the chamber, there were no significant changes in R and I. These findings are in contrast to other studies using a concentration of ethanol as high as 20 % [7,14] but they are in accord with the report by Saario et al [15] who reported that only concentrations greater than 30% elevated the R in the frog stomach. Submucosal ethanol exposure at 20% significantly decreased I but increased R. The depression of I is probably due to the interference of ion movement of electrical charges through cell membrane followed by a decrease in conductance (an increase in R), or dehydration of tissue, thus, leading to increase in R. It is believed that ethanol approaches the glandular mucosa more easily from the submucosal side (in the absence of epithelial barrier) than from the mucosal side, because the latter is protected by the epithelial cells and tight junctions.…”
Section: Discussioncontrasting
confidence: 56%
“…copeptic ceils were reported to be affected by the concentrations used in the present study [7,12,13].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Concentrations of alcohol less than about 10% do not appear to greatly damage the mucosa. Some of the effects of alcohol may be related to its osmotic activity, but the effects of ethyl alcohol do not seem to be exactly duplicated by other osmotically active agents [33,39,40]. Isotonic ethyl alcohol approximates only 1.6% v/v [40].…”
Section: Alcoholmentioning
confidence: 99%